CoronaVac-induced antibodies that facilitate Fc-mediated neutrophil phagocytosis track with COVID-19 disease resolution - Chuang Li; Jie Yu; Rahma Issa; Lili Wang; Mingzhe Ning; Shengxia Yin; Jie Li; Chao Wu; Yuxin Chen (Emerging Microbes and Infections)
Although severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants raise concerns about decreased vaccine efficacy, vaccines continue to confer robust protection in humans, implying that immunity beyond neutralization contributes to vaccine efficacy. In addition to neutralization, antibodies can mediate various Fc-dependent effector functions, including antibody-dependent cellular phagocytosis (ADCP), antibody-dependent neutrophil phagocytosis (ADNP) and antibody-dependent cellular cytotoxicity (ADCC). However, the specific role of each Fc-mediated effector function in contributing to COVID-19 disease attenuation in human remains unclear. To fully define the potential immune correlates of Fc-mediated effector functions, we comprehensively analysed the above Fc-mediated effector functions in two study cohorts. In the CoronaVac vaccinee cohort, individuals without breakthrough infection exhibited higher levels of ADCP and ADNP activities with a greater degree of cross-reactivity compared to those who had breakthrough infection. A predictive model was established incorporating ADNP activity and IgG titre, achieving an area under the curve (AUC) of 0.837. In the COVID-19 patient cohort, BA.5-specific ADCP and ADNP responses were significantly reduced in COVID-19 patients with fatal outcomes compared to milder outcomes. The prognostic model incorporating WT, BA.5, and XBB.1.5 spike-specific ADNP demonstrated effective predictive ability, achieving an AUC of 0.890. Meanwhile, transcriptomic analysis of peripheral blood mononuclear cells (PBMCs) from COVID-19 patients in the acute phases of infection highlighted remarkably upregulation of neutrophil activity and phagocytic function, further reinforcing the essential role of ADNP. Collectively, our findings underscored Fc-mediated effector activities, especially neutrophil phagocytosis, as significant antibody biomarkers for the risk of SARS-CoV-2 breakthrough infection and COVID-19 prognosis.